Correlation between the Degree of Glycocalyx Damage and the Incidence of Acute Kidney Injury in Sepsis Patients in the Intensive Care Unit: A Review of Syndecan-1 and sICAM-1 - Nurdin, Haizah; Arif, Syafri Kamsul; Tanra, A. Husni; Ahmad, Muh. Ramli; Wiryana, Made; Massi, Muh. Nasrum; Rasyid, Haerani; Bukhari, Agussalim (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstracts Objective: This study aims to know the correlation between the degree of glycocalyx damage and the incidence of Acute Renal Injury (AKI) in sepsis patients in the intensive care unit. In this study, a review of Syndecan-1 and sICAM-1 marker represented the severity of glycocalyx damage. Furthermore, the researchers wanted to see whether this marker in the serum of septic patients could predict the occurrence of AKI in the future of septic patients in the ICU. Design: This study is a prospective cohort nested-case control study, a case-control study conducted in a cohort population. Setting: This research has been carried out in the ICU, both RSPTN UNHAS and Dr. Wahidin Sudirohusodo Makassar. Syndecan-1 and sICAM-1 examination was carried out in the Hasanuddin University Hospital laboratory. Patients and participants: The sample was taken from septic patients treated in the ICU of RSPTN UNHAS and Dr. Wahidin Sudirohusodo Makassar admitted in January 2021. The sample selection was carried out consecutively, namely the selection of respondents based on the arrival of patients treated in the ICU until fulfilled. Measurement and Results: Data analysis in this study used the Mann-Whitney and Unpaired T-test. There was a significant difference in serum syndecan-1 levels between the two groups on day 0 and day 3 of ICU admission and changes from day 0 to day three. However, there was no significant relationship between sICAM-1 level in the two groups on day 0 and day 3 of ICU admission likewise its changes. Changes in syndecan-1 levels between the two groups were significantly different through the unpaired T-test. Conclusions: In this study, syndecan-1 levels can be used to predict the occurrence of AKI in the future for septic patients, while sICAM-1 is not statistically significant in predicting the occurrence of AKI among septic patients. Syndecan-1 is vital in the glycocalyx damage and helps predict clinical outcomes in patients with AKI.